Systematic Application of the Qualitative Evaluation of Cardápio Preparations (Aqpc) as an Instrument for the Analysis of two Food and Nutrition Units in Belém, Pa, Brazil - , Hanna Karyna Pinheiro de Oliveira; , Suenne Taynah Abe Sato; , Rosa Beatriz Monteiro Souza (Archives of Current Research International, 2020)
The qualitative assessment of preparation menu (AQPC) consists of a qualitative analysis of the menu composition regarding colors, preparation techniques, combinations, leafy offerings, fruits, sweets, types of meat and foods rich in sulfur. It is an important aid tool in the development of healthy and balanced menus. The objective of this study is to evaluate the quality of the menu of Food and Nutrition Units (UAN) through the AQPC method, to evaluate the main cooking methods of the main dishes, the main side dishes and types of proteins served and to classify the results of the application of the method. The data were tabulated in relation to the total days of the analyzed menus. The results showed percentages indicative of the nutritional quality of the menus. There was a high frequency of leafy leaves (59.1%) in both, being classified as ‘’Regular’’; with respect to colors, the university restaurant (UR) was classified as “Regular” (27.3%) and the RP as “Good” (18.2%); both restaurants were “Regular” in terms of sulfur-rich food, but ‘‘Great’’ in terms of fruit. Sweets were offered only in the RP, but at a low frequency (4.5%). There was no appearance of sweet + frying on both menus. In both restaurants, a high frequency of fried foods (59.1%) and fatty meats (40.9%) was observed. Regarding the meat preparation techniques, the roast and boil forms were verified only in the UR (31.8% and 4.5% respectively) and grilled and steamed only in the RP (4.5% and 9.1% respectively). The RP had a higher frequency of fried preparations (54.5%), stew (27.3%), whereas the stew was more frequent in the RP (40.9%). Regarding the types of proteins served, red meat was the most served type (UR, 72.7% and RP, 59.1%), chicken and fish were served more frequently in RP (40.9% and 4.5%, respectively). The main side dishes were rice, beans and flour, and most often they were served together both in the UR (72.7%) and in the RP (81.8%). It is concluded that the menus offer leafy and fruit in ideal quantities, but there is a high frequency of fatty meats and fried foods. In general, the AQPC method is a good tool to assist the nutritionist in the global and qualitative assessment of menus.